Dilemmas of Reconciliation : Cases and Concepts. - Prager, Carol (Wilfrid Laurier University Press, 2006)
How can bitter enemies who have inflicted unspeakable acts of cruelty on each other live together in peace? At a time in history when most organized violence consists of civil wars and when nations resort to genocidal policies, when horrendous numbers of civilians have been murdered, raped, or expelled from their homes, this book explores the possibility of forgiveness. The contributors to this book draw upon the insights of history, political science, philosophy, and psychology to examine the trauma left in the wake of such actions, using, as examples, numerous case studies from the Holo.